High sodium intake during postnatal phases induces an increase in arterial blood pressure in adult rats. Issue 12 (28th December 2014) - Moreira, M. C. S.; da Silva, E. F.; Silveira, L. L.; de Paiva, Y. B.; de Castro, C. H.; Freiria-Oliveira, A. H.; Rosa, D. A.; Ferreira, P. M.; Xavier, C. H.; Colombari, E.; Pedrino, Gustavo R.
<x content-type="archive" xml:space="preserve">Abstract</x> Epigenetic studies suggest that diseases that develop in adulthood are related to certain conditions to which the individual is exposed during the initial stages of life. Experimental evidence has demonstrated that offspring born to mothers maintained on high-Na diets during pregnancy have higher mean arterial pressure (MAP) in adulthood. Although these studies have demonstrated the importance of prenatal phases to hypertension development, no evidence regarding the role of high Na intake during postnatal phases in the development of this pathology has been reported. Therefore, in the present study, the effects of Na overload during childhood on induced water and Na intakes and on cardiovascular parameters in adulthood were evaluated. Experiments were carried out in two groups of 21-d-old rats: experimental group, maintained on hypertonic saline (0·3 m-NaCl) solution and food for 60 d, and control group, maintained on tap water and food. Later, both groups were given water and food for 15 d (recovery period). After the recovery period, chronic cannulation of the right femoral artery was performed in unanaesthetised rats to record baseline MAP and heart rate (HR). The experimental group was found to have increased basal MAP (98·6 (sem 2·6) v. 118·3 (sem 2·7) mmHg, P< 0·05) and HR (365·4 (sem 12·2) v. 398·2 (sem 7·5) beats per min, P< 0·05). There was a decrease in the baroreflex index in the experimental group when compared with that in the control group. A water and Na intake test was performed using furosemide. Na depletion was found to induce an increase in Na intake in both the control and experimental groups (12·1 (sem 0·6) ml and 7·8 (sem 1·1), respectively, P< 0·05); however, this increase was of lower magnitude in the experimental group. These results demonstrate that postnatal Na overload alters behavioural and cardiovascular regulation in adulthood.